Laproscopic Management of Large Ovarian Cyst with Pregnancy: A Case Report: OVARIAN CYST WITH PREGNANCY: A CASE REPORT - Darji , Ankit (International Journal of Scientific Research and Management (IJSRM), 2020)
Background: Before a pregnant woman's baby birth, the incidence of cyst is the most common. Due to availability of quality antenatal ultrasound, ovarian cysts in the pregnant woman are diagnosed more frequently. The large (>5 cm) and complex cysts are symptomatic and it required to be managed by surgical intervention. Cyst might rupture, twist, or even cause problems during childbirth.Aims and objective: To bring relief to a primigravida with 16 weeks pregnancy after spontaneous conception, presented with complain of hugely distended abdomen with marked discomfort and to preserve her pregnancy.Case Report:Materials and Methods: A 26 year old pregnant woman with ovarian cyst was enrolled and treated through laparoscopic management.Results: After the laparoscopic removal of cyst the post-operative period of the pregnant woman was found uneventful. The pregnancy of the woman was progressed smoothly and there was no any complications during the pregnancy. Full term normal delivery (FTNVD) was occurred and the baby was healthy with weight of approximately 2.55 Kgs.Conclusion: Large ovarian cyst can be managed without disturbing the pregnancy and a complicated case can be transformed into a normal ante natal check-ups (ANC).